REFERENCE HAEMATOLOGICAL VALUES FOR FULL TERM HEALTHY NEWBORNS FROM RURAL SINDH, PAKISTAN - Pasha, Waseem; Ali, Waqar; Ahmed, Nayyer; Khattak, Abdul Latif; Idris, Muhammad; Nayyer, Zameer Ahmad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Normal values of complete blood counts show variation from region to region and between different ethnic groups. It is important to establish reference range for these values in our population for clinical use by our physicians. This descriptive cross sectional study aimed at establishing the normal reference values of complete blood counts in physically normal full term new-borns of Panu Aqil, Rural Sind, Pakistan. Methods: The study was conducted at Combined Military Hospital, Panu Aqil Cantonment, from January 2010 to March 2011, on 316 term normal neonates selected on the basis of gestational age of 37 weeks or more with uneventful antenatal period. During the initial 12 hours of delivery, 2 ml Cord blood was collected in bottle containing tripotassium ethylene diamine tetra acetic acid (K3EDTA) as the anticoagulant and Complete blood counts were performed by Sysmex KX-21 automated haematology analyser. Blood films were prepared and stained by Leishman stain. Results: The haemoglobin was mean±SD 15.4±1.9 g/dL. The Mean Corpuscular Volume (MCV) was 103.4±4.6 fL, while Mean Corpuscular haemoglobin (MCH) was 33.8±1.6 pg. The Red cell Distribution Width-CV (RDW-CV) was 18.5±1.8%. The total leukocyte count (TLC) was mean±SD 13.7±4.0x109 /L. The Absolute Neutrophil count (ANC) was mean±SD 7.7±3.0x109 /L. The Absolute Lymphocyte count (ALC) was mean±SD 5.1±1.8x109 /L. Platelet count was mean±SD 285±62x109 /L. Conclusion: Our values provide reference range for haematological values in healthy newborns of Panu Aqil, Rural Sindh, for clinical use by our physicians. Keywords: Healthy new-borns, haematological, reference values, Rural Sindh